2022
DOI: 10.3390/s22030717
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Random Forests (RF) for Regional and Local-Scale Wheat Yield Prediction in Southeast Australia

Abstract: Wheat accounts for more than 50% of Australia’s total grain production. The capability to generate accurate in-season yield predictions is important across all components of the agricultural value chain. The literature on wheat yield prediction has motivated the need for more novel works evaluating machine learning techniques such as random forests (RF) at multiple scales. This research applied a Random Forest Regression (RFR) technique to build regional and local-scale yield prediction models at the pixel lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 67 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…The results are consistent with those of [ 78 ]; who tested several classifiers for change monitoring and found that the SVM, which makes use of publicly available Landsat imagery, was the most effective. From multiple time-series of high-resolution remote-sensing images [ 79 ], implemented a change detection method using visual saliency and SVM. When it came to mapping forests, however, conventional classifiers actually had the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are consistent with those of [ 78 ]; who tested several classifiers for change monitoring and found that the SVM, which makes use of publicly available Landsat imagery, was the most effective. From multiple time-series of high-resolution remote-sensing images [ 79 ], implemented a change detection method using visual saliency and SVM. When it came to mapping forests, however, conventional classifiers actually had the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to ML classifiers that used commercially accessible remote sensing data like LiDAR and WorldView-3, the accuracy of using publicly available Landsat images to recognize forests was on par [ [78] , [79] ]. SVM's total accuracy only reached 82%, despite the excellent spatial resolution of the LiDAR, WorldView, and Rapid Eye images [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-quality research was published in this SI from researchers from various countries, including China, the USA, Slovenia, Spain, Germany, Brazil, Australia, and Singapore. The SI’s studies have been ordered following the application within the soil–plant–atmosphere continuum starting with the soil salinity precision monitoring using unmanned aerial vehicles (UAV) and multispectral imagery [ 1 ]; the evaluation of optical sensors for the diagnosis of nitrogen content for wheat plants [ 2 ]; the detection of root-knot nematode infestation in potato plants using hyperspectral imagery [ 3 ]; detection of powdery mildew using hyperspectral, thermal, and RGB imagery [ 4 ]; leaf area index estimations for wheat using hyperspectral reflectance data [ 5 ]; vineyard canopy characteristics and vigor assessment using UAV and satellite imagery [ 6 ]; estimation of crop vegetation parameters using satellite and UAV spectral remote sensing [ 7 ]; above-ground biomass estimation of oat plants using UAV remote sensing and machine learning [ 8 ]; wheat lodging estimation using multispectral UAV imagery and deep learning [ 9 ]; yield estimation for guinea grass using UAV remote sensing [ 10 ]; and wheat yield prediction from satellite imagery, meteorological data, and machine learning modeling [ 11 ].…”
mentioning
confidence: 99%
“…Deep learning based on convolutional neural networks (CNN) with different architectures to analyze RGB from a UAV platform was used to estimate dry matter yield for guinea grass resulting in correlation coefficients of 0.79 < R < 0.62 [ 10 ]. Furthermore, RF algorithms were also used for wheat yield prediction based on satellite-based NDVI combined with meteorological data in Australia, resulting in 0.89 < R2 < 0.42 for different locations [ 11 ].…”
mentioning
confidence: 99%